MENTORING OF CLASSROOM ACTION RESEARCH AND PUBLICATION OF SCIENTIFIC WORKS IN DEVELOPMENT OF SUSTAINABLE PROFESSION FOR ELEMENTARY SCHOOL TEACHERS - Wahyudi Wahyudi; Rokhmaniyah Rokhmaniyah; Kartika Chrysti Suryandari (Universitas Sebelas Maret, 2018)
The aims of service are: (1) describe the implementation of workshop activities and mentoring the implementation of classroom action research (CAR) in sustainable professional development for elementary school teachers, (2) improve the understanding and skills of CAR in Sustainable Professional Development for elementary School Teachers.This Community Service activity uses the transfer of science and technology from universities to stakeholders which includes workshops and mentoring to elementary school teachers in Kebumen district in 2018. The data analysis used is descriptive-qualitative which includes (1) data reduction, (2 ) data presentation, and (3) drawing conclusions or verification of data.The results of this activity are (1) workshop materials and mentoring include: (a) problem formulation techniques in CAR, (b) CAR proposal preparation techniques, (c) CAR implementation techniques, (d) CAR reporting techniques, (e) scientific publication writing techniques, and (f) teacher functional credit score promotion techniques. (2) Workshops and mentoring methods can improve CAR understanding and skills in sustainable professional development for elementary School Teachers